Investigating the Mothers' Challenges in the Socialization of Primary School Children in the Pandemic of COVID-19 - Shariatmadar, Asieh; Ebrahimi, Sargol; Shahin bana, Mahsa; Sheikhi-Fini, Nasim (Applied Family Therapy Journal (AFTJ), 2021)
Aim: Childhood is one of the most important life periods of individuals, and care and attention to the physical and psychological health of children affect their quality of life in adulthood. One of the important components of mental health is acquiring skills and social growth. The purpose of this study was to study the children socialization challenges during the pandemic of COVID-19. Methods: In this study, 12 working and housewife mothers were purposefully selected and interviewed by a semi-structured interview. Results: The findings of this study, which was analyzed by content analysis, resulted in eight main themes, which include: Lack of social attachment due to absence, Harmful virtual relationships, Mood and personality challenges, Disorder in the process of self-regulation cultivation, Lack of learning impulse inhibition, Learn to excel through immoral behavior, Maternal fusion and lack of child independence, and Reducing the supportive role of the mother and her burnout. Conclusion: The present study showed that the COVID-19 pandemic period and the restriction of children from being in social environments and interacting with others, their social development has faced challenges; therefore, it is suggested that future research be conducted in future research method to prevent the harmful effects of children's socialization challenges.